Effect of soil solarization on pathogenic potential and viability of Fusarium oxysporum f.sp. dianthi causing wilt in carnation - and HARENDER RAJ*, H.S. NEGI (Indian Phytopathology, 2013)
Fusarium wilt (Fusarium oxysporum f.sp. dianthi) is one of the most prevalent and damaging diseases of carnation in all parts of the world. Soil solarization with transparent polyethylene sheet and biodegradable plastic sheet (both of 25Î¼m thickness) for 40 days resulted in an increase of 5.6 and 3.0Â°C, respectively in average maximum soil temperature inside polyhouse. Soil solarization of the culture of wilt pathogen with same sheets at 5 cm soil depth for 40 days increased the incubation period of the disease by 47.10 and 33.86% and reduced the disease incidence by 81.82 and 63.63%, respectively in comparison to pathogen culture retrieved from unsolarized plots inside polyhouse at same depth after same duration. Soil solarization of the culture of wilt pathogen with transparent polyethylene sheet and biodegradable plastic sheet at 5 cm soil depth for 40 days also resulted in 84.43 and 68.84% reduction respectively, in viability of propagules of the wilt pathogen in comparison to unsolarized beds at same depth inside the polyhouse. These findings advocate the effectiveness of soil solarization against wilt pathogen inside the polyhouse.